1987
DOI: 10.1203/00006450-198709000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Intestinal Glycosyl-Transferase Activities

Abstract: ABSTRACT. The carbohydrate composition of some intestinal glycoproteins has been demonstrated previously to be modified during development. To evaluate the role of the enzymatic mechanisms of glycosylation, the activities of three soluble and microsomal glycosyl-transferases were studied during postnatal development in rat intestinal mucosa. Nonexistent as soluble forms in the cell sap from suckling rats, the membrane-bound N-acetylgalactosaminyl-, sialyl-, and fucosyl-transferases showed different activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Developmental-dependent changes in glycosylation have also been observed with dopamine transporters during postnatal maturation (Patel et al, 1994). The developmental regulation in glycosylation may be explained by the availability of different glycosyltransferases during ontogenesis (Biol et al, 1987); yet, the selectivity for this change in the post-translational modification of GLAST (but not other glutamate transporters) is unclear. In vitro studies have revealed that the extent of N-linked glycosylation has a negligible effect on the transport activity of GLAST expressed in Xenopus oocytes (Conradt et al, 1995).…”
Section: Differential Post-translational Modification Of Glast Duringmentioning
confidence: 94%
“…Developmental-dependent changes in glycosylation have also been observed with dopamine transporters during postnatal maturation (Patel et al, 1994). The developmental regulation in glycosylation may be explained by the availability of different glycosyltransferases during ontogenesis (Biol et al, 1987); yet, the selectivity for this change in the post-translational modification of GLAST (but not other glutamate transporters) is unclear. In vitro studies have revealed that the extent of N-linked glycosylation has a negligible effect on the transport activity of GLAST expressed in Xenopus oocytes (Conradt et al, 1995).…”
Section: Differential Post-translational Modification Of Glast Duringmentioning
confidence: 94%
“…Indeed, the increase in intestinal spermine level at weaning paralleled that of fucosyltransferase activity that is naturally observed at this period [8], and the appearance of fucoproteins in the brush border membranes [11].…”
Section: Discussionmentioning
confidence: 78%
“…A shift from a high sialylation before weaning to a high fucosylation of the glycan chains after weaning has been demonstrated in glycoproteins of purified brush border membranes [2][3][4] and in mucins [5] by various techniques, as well as in the apical and basolateral membranes of the epithelial cells by lectin cytochemistry [6]. This shift is accompanied by a parallel decline in the activity and the mRNA level of an α-2,6-sialyltransferase from birth to weaning time [7][8][9] and by a large increase in the activity of an α-1,2-fucosyltransferase just after weaning [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The microvillus membrane (MVM) lining the enterocytes contains con siderable amounts of carbohydrates [4], We have previously shown that surface-reactive carbohydrates, in particular sialic acid and fucose, undergo striking modifications dur ing postnatal development in rat intestine [5,6]. During early suckling period, the membrane is rich in sialic acid and contains low levels of fucose but the pattern is re versed on weaning [6], Biol et al [7,8] have described that the quality as well as the quantity of diet affects the glycosyl-transferase levels in intestine. Since milk is the sole source of nutrition for the developing pups during the suckling period and the composi tion of milk is altered in response to changes in the maternal nutrition [9,10], we studied the effect of feeding low-protein (LP) diet (8% protein) to lactating rats on the absorp tion of 125I-labelled proteins and the glycosy lation of intestinal microvillus membrane in suckling rats.…”
Section: Introductionmentioning
confidence: 99%